Neglected Trauma: The Lives of Women Dissidents and Émigrés in Daňa Horáková’s Memoirs - Antošíková , Lucie (Porównania, 2023)
At the end of the 1970s, the Czechoslovak State Security, under the banner of the so-called ASANACE (‘sanitation’) campaign, used brutal means to deport leading dissidents abroad and break up the domestic opposition. As a result, many cultural figures emigrated, among them Daňa Horáková, a philosopher and collaborator of Václav Havel. Drawing on her memoir and the testimonies of other Czech female dissidents (and émigrés), the text reflects on the difficulties that life in dissent brought to women, as well as the pitfalls in which women were most at risk of becoming traumatized. Among the most risky moments was emigration and the uprootedness associated with it. Against the backdrop of research on emigration and trauma in literature, the present study offers an interpretation of O Pavlovi as a testament to the destructive impact of power.